2016
DOI: 10.1155/2016/3939540
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of 2‐(4‐Hydroxyphenyl)amino‐1,4‐naphthoquinone on Endothelial Vasodilation in Rat Aorta

Abstract: The vascular endothelium plays an essential role in the control of the blood flow. Pharmacological agents like quinone (menadione) at various doses modulate this process in a variety of ways. In this study, Q7, a 2-phenylamino-1,4-naphthoquinone derivative, significantly increased oxidative stress and induced vascular dysfunction at concentrations that were not cytotoxic to endothelial or vascular smooth muscle cells. Q7 reduced nitric oxide (NO) levels and endothelial vasodilation to acetylcholine in rat aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 57 publications
(63 reference statements)
0
14
0
Order By: Relevance
“…Nevertheless, sodium nitroprusside (SNP), a NO donor compound, caused a complete vasodilation even in the presence of 10 −5 M Q7. These data were recently published from our laboratory [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, sodium nitroprusside (SNP), a NO donor compound, caused a complete vasodilation even in the presence of 10 −5 M Q7. These data were recently published from our laboratory [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, Q7 significantly increased lipid peroxidation (TBARS) and decreased the SOD-like activity in serum of rats. In previous studies, we demonstrated increased TBARS levels in rat aorta tissue [ 19 ] and in calf thymus DNA treated with Q7 [ 21 ]. These findings are in agreement with other reports showing that oral administration of high-dose ascorbate reduced the blood pressure and heart rate in dogs displaying ROS-induced myocardial damage [ 31 ].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations